A Dynamic Framework for Healthcare Monitoring using Wireless Sensor Network - Singh, Jaswinder; Sharma, Sandeep (International Journal of Computer Sciences and Engineering, 2019)
The communication technology is growing day by day to provide instant and enhanced medical facilities to patients regardless of their physical location. Patients can be monitored and provided with quick medication while they are on the move. The existing technology is also capable to provide self-monitoring. Self-monitoring means people can use wireless technology to monitor their health at home on daily basis. The existing system provides home based ECG monitoring that reads physiological data and then convert them into readable format. Internet of Things (IOT) is new era of telecommunication that provides smart communication between human and sensor devices through various wireless technologies such as Wi-Fi, RFID, Bluetooth and ZigBee. Our proposed dynamic framework facilitates people to connect and communicate with healthcare centres in dynamic way while they are moving out of their home location. Secondly, the proposed system also make use of advance data management technique known as NoSQL especially used for un-structured datasets generated through ECG, SCG and other vital parameters of human body with the help of sensor networks. The paper is organised into sections viz. introduction, existing work, use of IoTs in wireless healthcare monitoring systems, proposed system, implementation and conclusion.